Status of Geography Education in the Government Colleges and Universities in Kerala - Sarath Chandran; Achu A L and Sheeba V (Utopia of Global Education, 2018)
Geography education in government colleges and universities in Kerala became less importance in its inception than other subjects. Because of this, Kerala has less government colleges and universities which offer geography as a subject. In post graduate level geography has no specialisation in any fields like physical geography or human geography; this makes the students from Kerala has to compete with those students who are specialised in physical geography or human/social geography from other states for further researches. The present paper is emphasizing on the status of geography education in the government colleges and universities in Kerala. Primary and secondary data has used for the present paper. Several private colleges have come up in the state with geography courses, but poor students cannot afford the fee. In government sector most of the affiliated colleges which offer geography courses are located in Thiruvananthapuram District which shows a disparity in location of the colleges and discrimination towards the students, teachers and scholars of central Kerala and northern Kerala.